PERAN PENGETAHUAN, LOCUS OF CONTROL DAN SIKAP TERHADAP PERILAKU PETANI BAWANG MERAH DALAM PENGENDALIAN HAMA DI KABUPATEN SIGI - Kasman Jaya (Jurnal Agrotech, 2018)
Onion farmers role in Sigi central Celebes as the main actor to maintain the natural resource is much determining the sustainability of future agriculture. Therefore, the farmer behavior on pest controlling is need to be improved and developed, also about the factors impacted. This study is aim to learn direct effect of locus of control and the manner towards onion farmer behavior on pest controlling in Sigi. To answer the purpose that has been told previously, we are going to do several step which is integrated to one another and systematic to gain the aim. This research is a kind of survey research and correlation ex-post facto. Respondents is the onion farmers in Sigi Biromaru as 200 farmers which obtain by proportional simple sampling principle. Primer data is obtained by several instrument such as; a). queisioner, b). test, c). observation, and d).in- depth interview. The first instrument used would be validity and reliability test. Description analysis is used to serve the data, size data, size central, and also dissemination size. Inferential analysis is used to examine the hypothesis with path analysis. The result of the study prove that farmer cognition about Integrated Pest Controlling (IPC) positively impact and significantly towards farmer behavior on pest controlling using IPC principle. Locus of control positively directly effect and significantly towards farmer behavior on pest controlling using IPC principle. Farmer cognition about integrated pest controlling and locus of control positively effect to farmer manner in Oloboju village. Farmer cognition about IPC, locus of control , and manner positively effect towards the farmer behavior on pest controlling. Farmer cognition and locus of control indirectly effect through farmer manner toward farmer behavior on IPC. This means the proliferation of farmer cognition about IPC and locus of control through farmer manner would triggered a change of farmer behavior on pest controlling and appropriate to IPC principle